تطور الاهتمام بالحيوان - أحمد رقــــــــادي (Institut PTIQ Jakarta, 2019)
I have dwelled mainly legislation of the Arab and western advocating the need for the protection of animals and welfare, the con-servation of functioning’s, rights, even imagined to some engaged in Islamic studies from the non-specialist said these calls the product of the times and human development in general, need to search the examiner in human heritage in general, and the Islamic world in particular, let us look at the development of animal attention both in religions, prohibits the publication of Christianity or, in some positive laws and the Old Town as laws of the ancient Romans, the laws of ancient Persia, and the laws of the Central Aruba, then look at the interest of Islam to animals both in terms of the attention of the Islamic sources, or to the attention of the Koran, and then conclude it compared to some moral values and educational which contribute to the protection of animals